Calvarial bone cavernous hemangioma with intradural invasion: An unusual aggressive course—Case report and literature review - Nasi, Davide (Int J Surg Case Rep, 2016)
INTRODUCTION: Cavernous hemangioma of the skull is a rare pathological diagnosis, accounting for 0.2% of bone tumors and 7% of skull tumors. Usually calvarial bone cavernous hemangioma are associated with a benign clinical course and, despite their enlargement and subsequent erosion of the surrounding bone, the inner table of the skull remains intact and the lesion is completely extracranial. PRESENTATION OF A CASE: The authors present the unique case of a huge left frontal bone cavernous malformation with intradural extension and brain compression determining a right hemiparesis. DISCUSSION: Calvarial cavernous hemangiomas are benign tumors. They arise from vessels in the diploic space and tend to involve the outer table of the skull with relative sparing of the inner table. More extensive involvement of the inner table and extradural space is very unusual and few cases are reported in literature. To the best of our knowledge, intradural invasion of calvarial hemangioma has not been previously reported. CONCLUSION: Our case highlights the possibility of an aggressive course of this rare benign pathology.